The effect of using Clinical nursing practice on the knowledge and self-care practice of patients receiving intravitreal injection - duangphrom, Malee; Hankumphorn, Siriwan; khuankhway, Thipawan (Journal of Health Sciences Sukhothai hospital, 2026)
Background: Intravitreal injection of bevacizumab (Avastin) is commonly used in the treatment of retinal diseases. Appropriate patient education and self-care are essential for preventing complications, particularly endophthalmitis. Nursing practice guidelines may improve patient knowledge and promote appropriate self-care behaviors after treatment. Objective: aimed to compare mean knowledge and self-care practice scores between patients receiving a nursing practice guideline for intravitreal Avastin injection and those receiving routine nursing care. Methods: Incidence of endophthalmitis within one month after injection. The sample included patients with retinal diseases attending the ophthalmology outpatient department at Sukhothai Hospital. The control group (n = 30) received routine care during, and the experimental group (n = 30) received care based on the nursing practice guideline during. The instruments demonstrated good content validity (IOC > 0.50) and acceptable reliability. Data were analyzed using descriptive statistics, independent t-test, and Fisher’s exact test. Results: showed that the experimental group had significantly higher mean knowledge and self-care practice scores than the control group (p < 0.05). No cases of endophthalmitis were found in either group after intravitreal Avastin injection. Conclusion: the nursing practice guideline improved patients’ knowledge and self-care practices. It should be applied in clinical practice to promote patient safety and effective self-care following treatment. Results The study revealed that the mean knowledge score of the experimental group (patients who received nursing care based on the guidelines for patients receiving intravitreal Avastin injection) was significantly higher than that of the control group (patients who received standard nursing care) (p < 0.05). This indicates that the nursing guidelines had a positive impact on the knowledge of patients receiving intravitreal Avastin injection. Similarly, the mean behavior score of the experimental group was significantly higher than that of the control group (p < 0.05). This suggests that the nursing guidelines also had a positive effect on the behavior of patients receiving intravitreal Avastin injection. However, the incidence of endophthalmitis (eye infection) within one month after the injection did not differ significantly between the experimental and control groups (p > 0.05). This implies that the nursing guidelines did not influence the infection rate. Conclusion The nursing guidelines for patients receiving intravitreal Avastin injection were found to have a positive impact on the knowledge and behavior of patients. Patients who received nursing care based on these guidelines demonstrated significantly higher levels of knowledge and better adherence to recommended self-care practices compared to those who received standard nursing care. However, the nursing guidelines did not influence the incidence of endophthalmitis within one month after the injection.